A generic, semi-empirical approach to the stochastic modelling of bath-type pyrometallurgical reactors - Eksteen, Jacobus Johannes; Reuter, M. A.; Bradshaw, S. M. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD)--University of Stellenbosch, 2004.